Effects of season and antler growth on carcass traits and meat quality in wild male red deer harvested by selective stalking - Martina Pérez Serrano; José Manuel Lorenzo; Roberto Bermúdez; Laura Purriños; Yolanda Fierro; Andrés José García; Datao Wang; Nicolás Alegría-Aravena; Louis Chonco; Tomas Landete-Castillejos (PLoS ONE, 2026)
Seasonal variation in temperate ecosystems influences food availability and the energetic demands associated with thermoregulation and reproduction, shaping physiological traits such as meat composition in wild animals. However, the specific effects of seasonality on meat quality in wild red deer remain insufficiently understood. This study evaluated how seasonality —represented by hunting month (September, January, April, and June)— affects the quality of the Longissimus thoracis et lumborum muscle in 32 adult wild male red deer harvested under minimal stress conditions. We hypothesized that seasonal fluctuations in diet and physiological requirements, particularly those linked to antler growth, would generate measurable differences in carcass traits and meat composition. Deer hunted in September (late summer) showed the highest carcass weight and yield, whereas the lowest values occurred in January (mid-winter) and June (early summer; p < 0.001). Intramuscular fat content was also greatest in September, with significant differences compared to April (p < 0.05). Additional seasonal effects were detected for pH at 72 h post-mortem (pH₇₂), shear force, and fatty acid profile (p < 0.05), indicating that muscle metabolism and textural properties vary across the year. Mineral composition exhibited a distinct pattern, suggesting a stronger association with skeletal mobilization during antler growth than with dietary changes. Mineral composition patterns were consistent with seasonal skeletal mobilization during antler growth: Ca and Mg were higher in April; Fe and Zn were lower in April and June. Overall, these findings demonstrate that both season and antler-growth effort affected meat quality and composition in wild male red deer, providing new insights into nutritional ecology and game meat quality.